Tunable First-Order Resistorless All-Pass Filter with Low Output Impedance - Parveen Beg (The Scientific World Journal)
This paper presents a voltage mode cascadable single active element tunable first-order all-pass filter with a single passive component. The active element used to realise the filter is a new building block termed as differential difference dual-X current conveyor with a buffered output (DD-DXCCII). The filter is thus realized with the help of a DD-DXCCII, a capacitor, and a MOS transistor. By exploiting the low output impedance, a higher order filter is also realized. Nonideal and parasitic study is also carried out on the realised filters. The proposed DD-DXCCII filters are simulated using TSMC the 0.25 µm technology.